CLARITY and Light-Sheet microscopy sample preparation in application to human cerebral organoids - T. A. Shnaider; I. E. Pristyazhnyuk (Вавиловский журнал генетики и селекции)
Cerebral organoids are three-dimensional cell-culture systems that represent a unique experimental model reconstructing early events of human neurogenesis in vitro in health and various pathologies. The most commonly used approach to studying the morphological parameters of organoids is immunohistochemical analysis; therefore, the three-dimensional cytoarchitecture of organoids, such as neural networks or asymmetric internal organization, is difficult to reconstruct using routine approaches. Immunohistochemical analysis of biological objects is a universal method in biological research. One of the key stages of this method is the production of cryo- or paraffin serial sections of samples, which is a very laborious and time-consuming process. In addition, slices represent only a tiny part of the object under study; three-dimensional reconstruction from the obtained serial images is an extremely complex process and often requires expensive special programs for image processing. Unfortunately, staining and microscopic examination of samples are difficult due to their low permeability and a high level of autofluorescence. Tissue cleaning technologies combined with Light-Sheet microscopy allows these challenges to be overcome. CLARITY is one of the tissue preparation techniques that makes it possible to obtain opaque biological objects transparent while maintaining the integrity of their internal structures. This method is based on a special sample preparation, during which lipids are removed from cells and replaced with hydrogel compounds such as acrylamide, while proteins and nucleic acids remain intact. CLARITY provides researchers with a unique opportunity to study three-dimensional biological structures while preserving their internal organization, including whole animals or embryos, individual organs and artificially grown organoids, in particular cerebral organoids. This protocol summarizes an optimization of CLARITY conditions for human brain organoids and the preparation of Light-Sheet microscopy samples.